Предмет: Алгебра, автор: liaseriously

Помогите !!!! Первый вариант!!! Срочно !!!

Приложения:

Ответы

Автор ответа: sangers1959
1

Объяснение:

1)

(\sqrt{5-2\sqrt{6} }+\sqrt{5+2\sqrt{6} }  )^2=(\sqrt{5-2\sqrt{6} })^2+2*\sqrt{5-2\sqrt{6} }* \sqrt{5+2\sqrt{6} }+(\sqrt{5+2\sqrt{6} } )^2=\\=5-2\sqrt{6} +2*\sqrt{(5-2\sqrt{6})*(5+2\sqrt{6} ) } +5+2\sqrt{6} =10+2*\sqrt{5^2-(2\sqrt{6} })^2 =\\\\=10+2*\sqrt{25-24} =10+2*\sqrt{1} =10+2=12.

2)

\sqrt[6]{(6-\sqrt{5})^6 } +\sqrt[8]{(1-\sqrt{5})^8 }=|6-\sqrt{5}|+|1-\sqrt{5}| =6-\sqrt{5}+\sqrt{5} -1=5.

Похожие вопросы
Предмет: Математика, автор: sayanmuratbek899